ANALISIS KETERAMPILAN MEMBACA PERMULAAN SISWA KELAS III DI SDN CAKUNG TIMUR 01 - Halizah, Firdha; Hasanah, Uswatun; Paulus Mbette, Petrus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the beginning reading skills of third-grade students at SDN Cakung Timur 01, who still face various learning challenges. The research aims to analyze the initial reading abilities of these third-grade students. Using a descriptive qualitative approach, data was collected through classroom observations and in-depth interviews. The findings reveal that while most students demonstrate adequate letter recognition, they encounter difficulties in proper word pronunciation, appropriate intonation, and reading fluency. Some students also struggle with self-confidence when reading aloud in class. Contributing factors include limited vocabulary, insufficient reading practice at home, and less varied teaching methods. The study highlights the need for a more comprehensive instructional approach to enhance early reading skills.